Verifying the Effects of Risk Variables on Return Volatility of Sector Price Indices in the Nigeria Stock Exchange - Nnenna, Okoli Margaret (Asian Economic and Financial Review, 2012)
The aim of this paper is to determine whether risk variables in particular interest rate and exchange rate play any important role in predicting sector price indices in the stock market. The stock market indices used include All-share index, banking index, insurance index, food and beverage index and oil and gas index .Index return and volatility is estimated using GARCH (1, 1).The findings revealed that exchange rate has a high negative influence on All-share index (ASI) and food and beverage index (FBI), while interest rate has a high significant negative impact on Oil and Gas Index (OGI). The variance of these indices also varies overtime. In other words, these indices exhibit volatility clustering. Worthy of note is that exchange rate (EXR) affects the volatility of the Food /Beverage index. It therefore implied that investors should watch this trend in return volatility changes before choosing their portfolio of investment for better risk management.